2021
DOI: 10.1111/mve.12538
|View full text |Cite
|
Sign up to set email alerts
|

I've got you under my skin: inflammatory response to elephant seal's lice

Abstract: Seals (Phocidae) undergo an annual cycle of moulting that implies hair regeneration, and in the case of southern elephant seals, it also involves the superficial strata of the epidermis. Therefore, surviving the moulting period is crucial for their obligate and permanent ectoparasites. Throughout evolutionary time, sucking lice (Echinophtiriidae) have developed morphological, behavioural and ecological adaptations to cope with the amphibious lifestyle of their hosts. Lepidophthirus macrorhini, the Southern ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Probably, these legs play a sensory role in insects where, according to the literature, eyes are absent [4,19,20]. However, the first pair of legs of L. macrorhini is robust, and the tarsal claws are modified into well-developed hooks [21]. It has been suggested that this species utilizes its claws to perforate the skin and dig into the host epidermis, in order to stay attached during elephant seal molting [21].…”
Section: Morphological Adaptationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably, these legs play a sensory role in insects where, according to the literature, eyes are absent [4,19,20]. However, the first pair of legs of L. macrorhini is robust, and the tarsal claws are modified into well-developed hooks [21]. It has been suggested that this species utilizes its claws to perforate the skin and dig into the host epidermis, in order to stay attached during elephant seal molting [21].…”
Section: Morphological Adaptationsmentioning
confidence: 99%
“…However, the first pair of legs of L. macrorhini is robust, and the tarsal claws are modified into well-developed hooks [21]. It has been suggested that this species utilizes its claws to perforate the skin and dig into the host epidermis, in order to stay attached during elephant seal molting [21]. Regarding the absence of eyes, a series of studies in different species is required to determine the presence of specific structures or pigments capable of detecting light.…”
Section: Morphological Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seal louse coevolved with terrestrial ancestors of seals from land into the marine environment millions of years ago 9 , 17 – 19 , hence the seal louse plays an important role as potential vector for a variety of infectious pathogens such as viruses and bacteria 20 , 21 and heartworms ( Acanthocheilonema spirocauda ) 11 , 22 24 . Because prevalence and intensity of ectoparasite infection are important biological indicators for predicting host health and inferring evolution 11 , 25 , 26 , precise information on seal louse infection parameters in vulnerable aquatic wildlife are crucial and of parasitological and veterinary relevance 24 , 27 .The seal louse developed biomechanical and physical adaptations for attachment and respiration in the marine environment 15 , 28 , 29 to sustain high pressure, drag forces, and hypoxemia 30 . The sampling of live lice is relevant for experiments on respiration, to investigate feeding and attachment adaptations 29 and reproductive processes in vitro.…”
Section: Introductionmentioning
confidence: 99%